Making contact: charge transfer during particle-electrode collisions - Rees, N; Zhou, Y; Compton, R (2012)
The study of impact processes between particles and electrode surfaces is less than 20 years old, and has recently received added impetus due to the current intense interest in the chemistry of nanoparticles. In this review, we briefly appraise the historical results and recent developments in this field, and consider its potentially wide-ranging applications. © 2012 The Royal Society of Chemistry.